Barriers and facilitators to implementing trauma registries in low- and middle-income countries: Qualitative experiences from Tanzania - Hendry R. Sawe; Nathanael Sirili; Ellen Weber; Timothy J. Coats; Lee A. Wallis; Teri A. Reynolds (African Journal of Emergency Medicine, 2020)
Background: The burden of trauma in low and middle-income countries (LMICs) is disproportionately high: LMICs account for nearly 90% of the global trauma deaths. Lack of trauma data has been identified as one of the major challenges in addressing the quality of trauma care and informing injury-preventing strategies in LMICs. This study aimed to explore the barriers and facilitators of current trauma documentation practices towards the development of a national trauma registry (TR). Methods: An exploratory qualitative study was conducted at five regional hospitals between August 2018 and December 2018. Five focus group discussions (FGDs) were conducted with 49 participants from five regional hospitals. Participants included specialists, medical doctors, assistant medical officers, clinical officers, nurses, health clerks and information communication and technology officers. Participants came from the emergency units, surgical and orthopaedic inpatient units, and they had permanent placement to work in these units as non-rotating staff. We analysed the gathered information using a hybrid thematic analysis. Results: Inconsistent documentation and archiving system, the disparity in knowledge and experience of trauma documentation, attitudes towards documentation and limitations of human and infrastructural resources in facilities we found as major barriers to the implementation of trauma registry. Health facilities commitment to standardising care, Ministry of Health and medicolegal data reporting requirements, and insurance reimbursements criteria of documentation were found as major facilitators to implementing trauma registry. Conclusions: Implementation of a trauma registry in regional hospitals is impacted by multiple barriers related to providers, the volume of documentation, resource availability for care, and facility care flow processes. However, financial, legal and administrative data reporting requirements exist as important facilitators in implementing the trauma registry at these hospitals. Capitalizing in the identified facilitators and investing to address the revealed barriers through contextualized interventions in Tanzania and other LMICs is recommended by this study.